GIS in Architectural Teaching and Research: Planning and Heritage - Bertha Santos; Jorge Gonçalves; Ana M. Martins; Maria T. Pérez-Cano; Eduardo Mosquera-Adell; Despina Dimelli; Apostolos Lagarias; Pedro G. Almeida (MDPI AG, 2021)
Geographical Information Systems (GISs) in architecture were initially limited to regional and urban development applications. Over recent years its potential has been recognized and its use has evolved to address urban planning and architectural heritage management subjects. Nevertheless, evidence shows that its use in architecture teaching is scarce and uneven. Directive 2007/2/EC, establishing the infrastructure for spatial information in the European Community (EU), is, in this way, an opportunity to develop a greater knowledge and application of GIS in the framework of higher education. In architecture, this can be achieved by problem solving based on real case scenarios, which can benefit from GIS-based techniques and analysis capabilities. In this paper, the authors aim to present a review of the use of GIS in teaching and research in architecture to assess its level in different European programmes. Experiences from three European universities (University of Seville, Spain, University of Beira Interior, Portugal, and Technical University of Crete, Greece), which are among the few in their respective countries that promote the inclusion of GIS in architectural education, particularly in the fields of urban and regional planning and architectural heritage, are compared and framed within the European scenario. The paper concludes with a reflection on the three universities' practice compared to the leading European architecture programmes listed in the main international university rankings. Main trends of future evolution on the use of GIS in architecture teaching are also presented.